Solution1.html

From HaskellWiki
Jump to: navigation, search
maternalGrandfather :: Sheep -> Maybe Sheep
maternalGrandfather s =
   return s    >>= \ms  ->
   mother ms   >>= \m   ->
   father m

fathersMaternalGrandmother :: Sheep -> Maybe Sheep
fathersMaternalGrandMother s =
   return s    >>= \ms  ->
   father ms   >>= \f   ->
   mother s    >>= \gm  ->
   mother gm

mothersPaternalGrandfather :: Sheep -> Maybe Sheep
mothersPaternalGrandfather s = 
   return s    >>= \ms  ->
   mother ms   >>= \m   ->
   father m    >>= \gf  ->
   father gf

Note: the returns are not not necessary; they are only used for the sake of the exercise.

An alternative solution without use of return:

maternalGrandfather :: Sheep -> Maybe Sheep
maternalGrandfather s =
   mother s    >>= \m   ->
   father m

fathersMaternalGrandmother :: Sheep -> Maybe Sheep
fathersMaternalGrandMother s =
   father s    >>= \f   ->
   mother s    >>= \gm  ->
   mother gm

mothersPaternalGrandfather :: Sheep -> Maybe Sheep
mothersPaternalGrandfather s = 
   mother s    >>= \m   ->
   father m    >>= \gf  ->
   father gf